Antioxidant Activity Test of Acetone and Ethanol Extracts of Cocoa (Theobroma cacao L.) Beans Husk - Siti S. K. Pandjo; Kasmudin Mustapa; Purnama Ningsih (Jurnal Akademika Kimia, 2021)
Cocoa beans husk is waste produced from the cocoa processing industry containing alkaloid, flavonoid, tannin, saponin, and triterpenoid compounds. This material has the potential to be used as a source of natural antioxidant compounds. This study aimed to determine the antioxidant activity of cacao beans husk extracts by comparing acetone and ethanol as solvents through the extraction process. This antioxidant activity was determined using the DPPH (1,1-diphenyl-2-picrylhydrazyl) test method measured by UV-Vis spectrophotometer after adding an extract of cocoa beans husk. The positive control was vitamin C, while the negative control was DPPH solution dissolved in ethanol. The results showed that the extract of cacao beans husk has more potent antioxidant activity with a lower IC50 value of 181.2 ppm, while the acetone extract has an IC50 value of 247.9 ppm